STUDYING THE EFFECT OF THE GLUTEN FRACTION OF PROTEIN ON THE HUMAN ORGANISM: https://doi.org/10.5281/zenodo.15260750 - Normatov , A.M.; Maxmudova , D.X.; Xoliqova , N.Gʻ. (International scientific and practical conference, 2025)
Gluten is one of the primary proteins found in wheat, barley, and other gluten-containing grains, and its consumption is an integral part of the dietary regime of many people. However, the effects of gluten on the human body and its adverse impact on individuals with conditions such as celiac disease and gluten allergy have been identified. Therefore, the identification of gluten fractions and the study of their effects on the body remain a pressing issue, contributing to the protection of public health. According to the primary recommendations of physicians for the treatment and prevention of these conditions, individuals must adhere to a strict gluten-free diet that eliminates foods containing gluten protein fractions from their diet. At the same time, it is emphasized that nutrition should remain healthy and balanced, including all essential nutrients, vitamins, minerals, and complete proteins.